2018
DOI: 10.14414/tiar.v8i1.1636
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Whistleblowers, Organizational Commitment, Ethical Climate Principles, and Self-Efficacy as Determinants of Fraud Disclosures

Abstract: Whistle-blowing is one of pro-social action done by organization members to give directions, procedures, or policies that have corrective impact on the organizations. The brave action to disclose fraud is determined by internal and external factors of individuals. This research is conducted to test factors that infl uence people to conduct whistleblowing, such as attitudes towards whistleblowers, ethical climate-principles, organization commitment, and self-effi cacy. This research also has objective to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
2
2
3
Order By: Relevance
“…Apart from that, there is also the possibility of apathy and fear of the risks faced by becoming a whistleblower. The results of this study are not consistent with Alleyne [21] and Hayati [53] but consistent with Sihombing [54], Ahmad [55], Aliyah [56] and Mesmer-Magnus [45].…”
Section: Hypothesis Testcontrasting
confidence: 69%
“…Apart from that, there is also the possibility of apathy and fear of the risks faced by becoming a whistleblower. The results of this study are not consistent with Alleyne [21] and Hayati [53] but consistent with Sihombing [54], Ahmad [55], Aliyah [56] and Mesmer-Magnus [45].…”
Section: Hypothesis Testcontrasting
confidence: 69%
“…First, this study examines the role of organizational ethical climate and whistleblowing behavior in Chinese SMEs. According to prior research, organizational ethical climate was found to have a positive effect on whistleblowing behavior [86,87]. Whereas, there is no direct effect in this study.…”
Section: Limitations and Future Researchcontrasting
confidence: 44%
“…Beberapa penelitian terdahulu telah mengkaji faktor-faktor yang memengaruhi internal whistleblowing di berbagai konteks, seperti BUMN [8], [9], perusahaan [10], sektor pemerintah [11], [12], [13], [14] dan pegawai pajak [15], [16]. Faktor yang memengaruhi intensi internal whistleblowing telah dikaji oleh peneliti terdahulu, seperti ethical climate [16] yaitu ethical climate-egoism, ethical climate-benevolence dan ethical climate-principle akan memengaruhi sikap pegawai ketika melihat suatu kejadian pada organisasinya.…”
Section: Pendahuluanunclassified
“…Faktor yang memengaruhi intensi internal whistleblowing telah dikaji oleh peneliti terdahulu, seperti ethical climate [16] yaitu ethical climate-egoism, ethical climate-benevolence dan ethical climate-principle akan memengaruhi sikap pegawai ketika melihat suatu kejadian pada organisasinya. Riset sebelumnya [8], [9] membuktikan bahwa ethical climateprinciple berpengaruh positif terhadap intensi whistleblowing pada karyawan BUMN. Namun dalam konteks ASN, ethical climate tidak berpengaruh terhadap intensi whistleblowing internal [17].…”
Section: Pendahuluanunclassified